2014
DOI: 10.1016/j.fluid.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and separation of CO2/CH4 mixtures using nanoporous adsorbents by molecular simulation

Abstract: We report a grand canonical Monte Carlo simulation study focused on the adsorption of CO 2 /CH 4 mixtures in different nanopore models that include pristine mesoporous carbons, carbon foams, carbon nanotubes (CNTs) and nanopore models modified with hydrophilic carboxylic groups. We report and discuss the selectivity of the different adsorbent morphologies under a wide range of temperature and pressure. Results show that the foam structures have the highest adsorption capacity of all pristine structures studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 45 publications
2
50
0
Order By: Relevance
“…According to Equation (4), we first determined the adsorption selectivity and diffusion selectivity of mixed gas in kerogen. In the process of adsorption equilibrium, we used the adsorption selectivity (Ssorp) to determine the adsorption capacity of the gas mixture [65,66] Diffusion selectivity refers to the ratio of mixture's fraction diffusion coefficient [67], the calculation formula is shown in Equation (5): Figure 8 shows the adsorption selectivity, diffusion selectivity and permeation selectivity of CH4/CO2 with different molar ratios in kerogen. …”
Section: Adsorption Diffusion and Permeation Selectivity Of Binary Gasmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Equation (4), we first determined the adsorption selectivity and diffusion selectivity of mixed gas in kerogen. In the process of adsorption equilibrium, we used the adsorption selectivity (Ssorp) to determine the adsorption capacity of the gas mixture [65,66] Diffusion selectivity refers to the ratio of mixture's fraction diffusion coefficient [67], the calculation formula is shown in Equation (5): Figure 8 shows the adsorption selectivity, diffusion selectivity and permeation selectivity of CH4/CO2 with different molar ratios in kerogen. …”
Section: Adsorption Diffusion and Permeation Selectivity Of Binary Gasmentioning
confidence: 99%
“…According to Equation (4), we first determined the adsorption selectivity and diffusion selectivity of mixed gas in kerogen. In the process of adsorption equilibrium, we used the adsorption selectivity (S sorp ) to determine the adsorption capacity of the gas mixture [65,66]:…”
Section: Adsorption Diffusion and Permeation Selectivity Of Binary Gasmentioning
confidence: 99%
“…The CO 2 molecules were modelled by the three-centre EPM2 (elementary physical model 2) model [28]. The CNTs were modelled in the same way as in our previous paper [29]: carbon atoms of CNTs were treated as neutral L-J interaction sites. The bond length of C-O in CO 2 was 0.1149 nm and the bond stretching parameter was 294.29 kcal/mol.…”
Section: Potential Modelsmentioning
confidence: 99%
“…20,[26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] Most of these simulation studies consider classical force fields, but ab initio calculations have also been reported. 19,27,42 The capacity of carbon nanotubes to adsorb pure CO 2 has been tested by computer simulations in isolated 19 and arrays of parallel SWCNTs, 20 as well as isolated 36 and parallel double-walled carbon nanotube bundles.…”
Section: Introductionmentioning
confidence: 99%
“…19,27,42 The capacity of carbon nanotubes to adsorb pure CO 2 has been tested by computer simulations in isolated 19 and arrays of parallel SWCNTs, 20 as well as isolated 36 and parallel double-walled carbon nanotube bundles. 38,40 On the other hand, CO 2 separation by carbon nanotubes from mixtures has been studied in CO 2 -CH 4 mixtures, 30,39 in presence of water 37 or in CO 2 -N 2 mixtures. 33 This latter study, relevant for CO 2 capture from flue gases, studied the effect of pressure, temperature, and bulk gas composition on the CO 2 adsorption in SWCNTs with diameters between 8 and 10 Å.…”
Section: Introductionmentioning
confidence: 99%